Telaah Substansi Mitigasi Bencana Geologi dalam RTRW Kota Gorontalo Tahun 2019–2039 - Amalia Putri Paputungan; Tanzilal Pena; Suci Rahmawati Mustapa; Candrawati Pulogu; Mohamad Saputra Hamzah; Sri Maryati; Ronal Hutagalung (Universitas Negeri Gorontalo, 2026)
Gorontalo City is an urban area vulnerable to geological and hydrometeorological hazards, including earthquakes, landslides, floods, coastal abrasion, and tsunamis. Spatial planning is an important instrument for disaster risk reduction through the regulation of disaster-prone areas, protected areas, and spatial utilization control. This study aims to examine the substance of geological disaster mitigation in Gorontalo City Regional Regulation Number 9 of 2019 concerning the 2019–2039 Spatial Plan. This research employed a qualitative approach using content analysis of the spatial planning document, particularly sections related to disaster-prone areas, active fault buffer zones, earthquake-prone areas, and zoning provisions. The findings show that the Gorontalo City Spatial Plan has accommodated disaster mitigation through the designation of disaster-prone areas, protection of conservation areas, control of cultivation activities, and provision of evacuation routes and spaces. However, these provisions still require more detailed technical elaboration, particularly regarding the spatial boundaries of active fault buffer zones, safe distances from fault lines, hazard classification, and technical requirements for development in disaster-prone areas. Therefore, strengthening detailed spatial plans, zoning regulations, integration of disaster hazard maps, and supervision of spatial utilization is essential to support safer and more sustainable urban development in Gorontalo City.Keywords: disaster mitigation, Spatial Plans (RTRW). The Gorontalo region's geological conditions are influenced by tectonic activity and the presence, active faults, earthquakes, spatial planning.